Take It Or Leave It: Hubungan Antara Pengembangan Karir, Kepuasan Kerja dan Turnover Intention dengan Entrepreneurship Intention Sebagai Variabel Moderasi Pada Karyawan Industri Logistik di Gresik Jawa Timur - Nur Cahyadi; Putra Panji Respati (Jurnal Manajerial, 2025)
Background – Business competition is getting tighter and more competitive, making the function of Human Resources (HR) in the service industry is one of the main factors to win the competition. Research object is a company in the field of logistics services and depends on quality human resources. However, the company is facing a high turnover problem. Aim – This study aims to determine the relationship between career development, job satisfaction and entrepreneurship intention as a moderating variable on turnover intention. Design / methodology / approach – This research is quantitative and data collection uses questionnaires and the sampling technique used is purposive sampling with the criteria that respondents work for at least one year. The sampling method was carried out up to 84 respondents and the analysis tool used was Partial Least Square (PLS). Findings – The results of this study include (1) The influence of career development variables on job satisfaction. (2) Job satisfaction affects on turnover intention. The last result is (3) Job satisfaction and entrepreneurship intention as moderating variables strengthen the relationship to the turnover intention variable. Research implication – This research can provide an overview for companies, especially in the logistics sector, regarding efforts to minimize the rate of employee resignation by paying attention to the career development system and job satisfaction.  Limitations – The limitation of this research is that the research was only conducted on one object, a logistics company located in Gresik, and the research study was conducted cross-sectionally, analyzing variable data a certain time across the entire predetermined sample population.